2015
DOI: 10.1038/srep17643
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid is a sperm motility inactivation factor in the sperm storage tubules

Abstract: Although successful fertilization depends on timely encounters between sperm and egg, the decoupling of mating and fertilization often confers reproductive advantages to internally fertilizing animals. In several vertebrate groups, postcopulatory sperm viability is prolonged by storage in specialized organs within the female reproductive tract. In birds, ejaculated sperm can be stored in a quiescent state within oviductal sperm storage tubules (SSTs), thereby retaining fertilizability for up to 15 weeks at bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 52 publications
5
67
0
2
Order By: Relevance
“…In our recent research, we found that lactic acid in the SST lumen immobilized the resident sperm through cytoplasmic acidification that led to the inactivation of dynein ATPase (Matsuzaki et al, 2015). In contrast, BisII-mediated sperm motility inactivation is not related to pH i ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…In our recent research, we found that lactic acid in the SST lumen immobilized the resident sperm through cytoplasmic acidification that led to the inactivation of dynein ATPase (Matsuzaki et al, 2015). In contrast, BisII-mediated sperm motility inactivation is not related to pH i ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…5A). Because high concentrations of lactate were detected in the seminal receptacle, this metabolite might help to sustain sperm survival under anaerobic conditions (31).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should address the molecular and cellular mechanisms of how squid spermatozoa are capable of storing glycogen at different levels. The physiological role of lactate efflux for sperm quiescence should also be considered in this species (31). These studies will open up new avenues in the field of andrology with the hope of developing treatments for human male infertility associated with flagellar motility deficiencies (39).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, sperm motility is regulated by various extracellular cues, such as peptides/proteins and steroids (Clapper & Epel, 1982;Matsuzaki et al, 2015;Oda et al, 1995;Olson et al, 2001;Osanai, Kasuga, & Aigaki, 1989;Pillai, Shields, Yanagimachi, & Cherr, 1993;Strünker et al, 2011;Ward, Brokaw, Garbers, & Vacquier, 1985;Yoshida, Ishikawa, Izumi, DeSantis, & Morisawa, 2002). Each cue is adapted to a species-specific reproductive mode to ensure successful fertilization.…”
Section: Introductionmentioning
confidence: 99%